Optimisation of the production of nanovesicles from phytopathogenic bacterial species - Lim, Matthew Segarra (Nanyang Technological University, 2023)
The use of bacteria derived nanovesicles (BDNs) for the development of medical treatments have been well documented in literature. However, the use of BDNs derived from phytopathogenic bacterial species for the treatment of plants has not yet been well studied. This project aimed to optimise a production protocol of mimetic extracellular vesicles from the bacterial species Pseudomonas Syringae using spin cups as an extrusion method, with the hope that it may be scaled up to an industrial level. The yield of extracellular vesicles by using a memetic production method was then compared against the vesicle yield that was naturally produced by Pseudomonas Syringae. It was found that both methods are similar in vesicle yields and that the use of spin cups to produce extracellular vesicles do not provide much of an advantage over the method used to produce BDNs naturally.